Association between fertility drugs and gynecologic cancers, breast cancer, and childhood cancers - Ayhan, A; Salman, MC; Celik, H; Dursun, P; Ozyuncu, O; Gultekin, M (Wiley, 2004)
Ovulation-inducing drugs have been widely used for various types of infertility since the beginning of 1960s and their use increases day by day parallel to the success achieved in fertility treatment. However, the researches performed in the last two decades have begun to discuss about the safety of these drugs and the risks associated with their use. Especially, the potential neoplastic effects of these drugs are increasingly questioned. The studies have discussed whether there is an association between the exposure to ovulation-inducing drugs and the incidence of various cancers. Moreover, several studies have been performed to reveal whether there is an increased risk of childhood cancers in children conceived after fertility treatment. The point we reached through the available data is that the risk of breast, uterine and invasive ovarian cancers is not increased, but the risk of borderline ovarian tumors might increase after such a therapy. The risk of cancer has been found similar for children conceived after fertility treatment and those conceived naturally. It should also be kept in mind that cancers are overdiagnosed in infertile women population because of the close medical surveillance, which may also contribute to the early detection of cancers. Although it is still early to state the last words on this topic, the possible association should be addressed when obtaining an informed consent before starting treatment.
Keywords: breast cancer; cervical cancer; childhood cancers; fertility treatment; infertility; ovarian cancer; ovulation induction; uterine cancer